Managing Rabies Cases with a One Health Approach in Various Countries: Literature Review - Salma Sabira; Helda; Gustia Arminda Siregar; Qonita Nur Salamah (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: More people die from rabies than from other zoonotic diseases worldwide each year, with an estimated 60,000 deaths attributable to the disease. The management of rabies epidemics in humans and animals is the main goal of the One Health approach's implementation. Reducing the risk of animal-to-human rabies transmission not only lessens the requirement for post-exposure vaccinations but also lessens the financial burden of rabies management in people. Objective: This review aims to provide a general overview and comparison of rabies control programs in various countries using the One Health approach. Method: PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) is used in the literature review. Using the Science Direct, Scopus, and Pubmed databases covering the years 2012–2022, look up library resources. Result: The results of the literature search with the keywords control, one health approach, and rabies were screened again according to the predetermined inclusion criteria and the publication time range of 2012–2022 until 10 suitable journals were obtained. With financial assistance from the European Union, a number of European nations initiated oral rabies vaccination (ORV) programs in foxes. The vaccine was given in bait form, effectively controlling vulpine rabies. The creation of ORV demonstrates that oral rabies vaccination for wildlife in Serbia was effective and was marked by a rise in the use of vaccine bait as well as an increase in the animal's immunological response. Consequently, until 2018, fewer instances of rabies were documented. Conclusion: With multisectoral support from partners in the government and non-government sectors, implementing One Health is one of the best ways to reduce rabies and guarantee community engagement and knowledge.